On positive periodic solutions of the time–space periodic Lotka–Volterra cooperating system in multi-dimensional media. (August 2023) - Du, Li-Jun
Abstract: This work is devoted to the study of the time–space periodic reaction–diffusion–advection Lotka–Volterra cooperating system in multi-dimensional media. By using the method of sub-super solutions and its associated iterations, we prove the existence and uniqueness of the positive periodic solution under appropriate conditions. Finally, we are able to derive the asymptotic behavior of the solutions to the associated Cauchy problem.